Cationic dye removal from aqueous solution by waste biomass produced from calcination treatment of rice bran. Issue 3 (September 2015) - Ogata, Fumihiko; Imai, Daisuke; Kawasaki, Naohito
Graphical abstract: Highlights: Amount adsorbed was in the order RB600 < RB800 < RB < RB1000. Amount of MB and CV adsorbed was related to the physical properties of adsorbents. Dyes adsorption processes onto RB should be regarded as physical adsorption. Abstract: Biomass-derived adsorbents, prepared from rice bran (RB) and treated by calcination at 600, 800, and 1000 °C (RB600, RB800, and RB1000), were characterized in terms of their properties. The adsorption of methylene blue (MB) and crystal violet (CV) on the biomass adsorbents was evaluated. The amount of MB and CV adsorbed was related to the physical properties of the adsorbent. For both dyes, the adsorption capacity increases with time, and the equilibrium time is about 8 and 48 h for uncalcined RB and RB1000, respectively. The adsorption kinetics of dyes is better described by a pseudo-second-order kinetic model. Moreover, the amount of MB or CV adsorbed onto uncalcined RB decreased with increasing temperature, whereas adsorption onto RB1000 increased with increasing temperature. The enthalpies implied by the temperature dependence were Δ H  = −4.89 to −54.77 kJ/mol and 11.13–50.21 kJ/mol, for uncalcined RB and RB1000, respectively, which suggested that the adsorption of the dyes onto uncalcined RB or RB1000 should be regarded as physical adsorption, or between physical adsorption and chemical adsorption but dominated by physical adsorption. The equilibrium data of dyes fitted well to the Freundlich adsorption isotherm models. The amount of dyes adsorbed onto uncalcined RB or RB1000 increased at approximately pH 6.0 or 10.0, respectively, which suggests that MB and CV were adsorbed on the surface of the adsorbent through interactions between the electrons of the negatively charged adsorbent surface and the cationic dyes in solution.